Impact of Air Intake Restriction on the Performance and Emissions of a Dual‑Fuel Ethanol‑Diesel Compression Ignition Engine - Rosa, Josimar Souza; de Souza, Túlio Augusto Zucareli; Hammes, Thomas; Telli, Giovani Dambros (New Energy Exploitation and Application, 2026)
In Brazil, diesel engines are widely used in freight transportation, particularly in the agricultural and agribusiness sectors, as well as in a significant portion of passenger transport. The main concern associated with these engines lies in the combustion of diesel fuel due to its harmful impacts on both the environment and human health. In order to mitigate these impacts, the replacement of diesel fuel, a fossil energy source, with renewable fuels has been extensively investigated. In this context, the present study evaluates the performance and emission characteristics of a single-cylinder diesel engine operating with partial substitution of diesel by ethanol. Ethanol was injected into the engine intake manifold, while diesel fuel was directly injected into the combustion chamber. Dual-fuel operation tests were conducted with the engine operating at the same power range (approximately 60% of its rated capacity), for four different ethanol flow rates and two distinct intake air flow rates. Overall, for all ethanol flow rates applied and for both adjusted intake air flow conditions, the results showed an increase in thermal efficiency of approximately 9% compared to conventional diesel operation. Regarding emissions, ethanol led to a maximum reduction of approximately 50% in exhaust gas opacity and about 22.8% in NOx emissions, but increased CO. The results indicate that ethanol, a widely commercialized fuel in Brazil, may represent a viable path towards reduced emissions in the transportation sector, while requiring very little modification in current diesel engines.